Initiatives of Community Radios in achieving Sustainable Development Goal related to Good Health & Well- Being: A Study of CRS KGMU Goonj. - Kastoori Singh Dr. Amar Pal Singh Dr.Kirti Vikram Singh (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2024)
Achieving the SDGs continues to remain a big challenge in developing country like India mainly due to the lack of effective & useful communication with the marginalized segment of the society. When we talk about reaching the last man, the role of CRs – that is considered as the third pillar of the broadcast media—cannot be overlooked. But, when we talk about SDG 3 i.e. Good Health and Well-being, the contribution of Community Radio Station which is being run by King George Medical University named ‘KGMU Goonj’ is immense.